Pengaruh Terapi Psikoreligius Terhadap Penurunan Tingkat Depresi Pada Lansia - Suryanti Suryanti; Dwi Ariani S (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Lower Extremity Elevation, Diabetic Ulcer Healing Process. People with Diabetes Mellitus have poor circulation, especially in areas far from heart, these causing the length of time of wounds healing. One of the interventions to improve the peripheral tissue perfusion of patients with Diabetic Ulcer is lower extremity elevation. The purpose of this research is to describe the characteristics of respondents, knowing Diabetic Ulcer healing process without lower extremity elevation, knowing Diabetic Ulcer healing process with lower extremity elevation and knowing the effectiveness of Diabetic Ulcer healing without lower extremity elevation and with lower extremity elevation. This research is to design a queasy experiment non-equivalent control group design and analysis data used Chi-Square test. Results of this research are the elevation of lower extremities more effectively to increased Ulcers Diabetic healing process. It’s evidenced by the Chi-Square test using Pearson Chi-Square analysis and obtained ρ = 0,027 and α = 0,05. Elevation of lower extremities more effectively to increased Diabetic Ulcer healing in patients with Diabetic Ulcer in Melati I RSUD Dr. Moewardi. Lower extremity elevation expects can be applied in patients with Diabetic Ulcer.